Hamzanwadi Dan Gerakan Kebangsaan Melalui Pendidikan Berbasis Lokal Bermatra Nasional - Khirjan Nahdi; Sitti Rohmi Djalilah; Musifuddin Musifuddin; M Deni Siregar (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
The purpose of this research is to find the thoughts, institutionalization, and agenda of the national movement carried out by Hamzanwadi in Lombok through education. This research uses the method of text documentation, context, and the relationship between the text and the community. The study data was collected through a disaggregated note technique on the proposal of a national hero for Hamzanwadi. Data were analyzed according to historical analysis and hermeneutics as historical and social studies. The results of this study are: 1) Hamzanwadi initiated national thinking through education and established educational institutions as a means of raising awareness of the importance of national independence; 2) Hamzanwadi labels educational institutions as Nahdlatul Wathan as a representation of the thoughts of the national movement or the movement of the homeland; 3) Hamzanwadi develops education for all by initiating equality education through educational institutions for women. It was concluded that, Hamzanwadi had initiated and carried out a national movement through education, institutionalized institutionalization as a representation of national thoughts and actions, and offered thoughts and actions of equality for men and women. Until now, these thoughts, actions and institutionalization are still known through the name of the Nahdlatul Wathan educational organization and institution as local treasures with national dimensions.